Fostering SDG Content Integration in the Economics and Business Undergraduate Curriculum: A Faculty-Driven Mapping Approach - Igor Vrečko; Maja Rožman; Karin Širec (Education Sciences)
The Faculty of Economics and Business (FEB UM) initiated a project to align its undergraduate study program with sustainable development principles. This involved mapping the Sustainable Development Goals (SDGs) within the curriculum, using recommended keywords and faculty assessments. The exercise aimed to objectively showcase current sustainability integration and to identify areas for enhanced sustainable practice infusion. The method entailed both the direct and indirect consideration of SDG content. This endeavor heightened faculty awareness and enthusiasm for incorporating the SDGs, highlighting the significance of aligning academic programs with global sustainability objectives. This study has offered a framework for similar institutions aiming to boost sustainability through curriculum mapping and active faculty engagement.